Effects of a methanolic fraction of soybean seeds on the transcriptional activity of peroxisome proliferator-activated receptors (PPAR) - Carrara,V.S. (2009)
Since the anti-inflammatory, antidiabetic and hypolipidemic effects of soy isoflavones may be mediated by activation of peroxisome proliferator-activated receptors (PPAR), the present study investigated whether the methanolic fractions obtained from soybean seeds (E1) and soybean seed coats with hypocotyls (E2) could influence PPARα, PPARγ and PPARβ/δ transcriptional activity. The isoflavones from E1 and E2 were quantified by HPLC analysis. E1 and E2 were rich in isoflavones (daidzin, glycitin, genistin, malonyldaidzin, malonylglycitin, malonylgenistin, daidzein, glycitein, and genistein). Moreover, E1 and E2 showed no evidence of genetically modified material containing the gene CP4 EPSPS. To investigate PPAR transcriptional activity, human promonocytic U-937 cells were treated with E1 and E2 (200, 400, 800, and 1600 µg/mL), positive controls or vehicle. Data are reported as fold-activation of the luciferase reporter driven by the PPAR-responsive element. Dose-response analysis revealed that E1 and E2 induced the transcriptional activity of PPARα (P < 0.001), with activation comparable to that obtained with 0.1 mM bezafibrate (positive control) at 1600 µg/mL (4-fold) and 800 µg/mL (9-fold), respectively. In addition, dose-response analysis revealed that E1 and E2 activated PPARβ/δ (P < 0.05), and the activation at 800 µg/mL (4- and 9-fold, respectively) was comparable to that of 0.1 mM bezafibrate (positive control). However, no effect on PPARγ was observed. Activation of PPARα is consistent with the lipid-lowering activity of soy isoflavones in vivo, but further studies are needed to determine the physiological significance of PPARβ/δ activation.